Terceirizaç\~ao no Brasil: Avaliaç\~ao do marco legal e esclarecimentos sobre o Projeto de Lei no 4.330/2004 - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Nowadays, in Brazilian parliament, there are several propositions able to enact a legislative regulation to outsourcing. Bill no 4.330/04 is just one of them - probably, the one far ahead in the lawmaking process. Is this the best option for regulating outsourcing? There is a harsh debate about this, involving mainly workers' and companies' representatives. Specifically from workers' point of view, there are aspects of Bill no 4.330/04 that may cause a lot of apprehension. Probably, additional studies should be made about this, before parliament's final deliberation. After all, outsourcing may pose many relevant impacts for Brazilian labor market, especially for workers.
Keywords: K00; K19; K31; 330; labor market; outsourcing; regulation